On the Rails Rambert on the Underground - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Rambert on the Underground PALABRAS CLAVE: Rambert Dance Company, metro, Canary Wharf Underground, station, performance, contemporary dance, outside the scenarios.
Dentro del apartado "Beyond the proscenium".